Genetics and Idiopathic Interstitial Pneumonias - Chu, Sarah G.; El-Chemaly, Souheil; Rosas, Ivan O. (Seminars in Respiratory and Critical Care Medicine, 2016)
Significant progress has been made in elucidating the genetics of parenchymal lung diseases, particularly idiopathic interstitial pneumonias (IIPs). IIPs are a heterogeneous group of diffuse interstitial lung diseases of uncertain etiology, diagnosed only after known causes of interstitial lung disease have been excluded. Idiopathic pulmonary fibrosis is the most common IIP. Through candidate gene approaches and genome wide association studies, much light has been shed on the genetic origins of IIPs, enhancing our understanding of risk factors and pathogenesis. However, significant work remains to be accomplished in identifying novel genetic variants and characterizing the function of validated candidate genes in lung pathobiology, their interplay with environmental factors, and ultimately translating these discoveries to patient care.
Keywords: interstitial pneumonia; IPF; surfactant protein; telomere; MUC5B